Inclusions. - Chicchi, Federico; Tucci, Antonio (Soft Power, 2018)
The paradigm based on the conceptual dichotomy between inclusion and exclusion – which has affected the modern era of political and legal thought – is definitely ineffective in portraying assets and institutions as well as political and social forms that currently frame the neoliberal governmentality.